Comparative Estimation of (a + b) Boswellic Acid and Curcumin from Marketed Herbal Antirheumatic Tablets - Wandhare, M.D.; Deokate, U.A.; Khadabadi, S.S.; Hadke, S.P.; Deore, S.L. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high-performance thin-layer chromatographic (HPLC) method was developed and validated for the quantitative estimation of boswellic acids in formulation containing Boswellia serrata extract (BSE). Simple extraction method was used for isolation of boswellic acid from formulation sample. The isolated samples were chromatographed by using RP-HPLC method on HiQ Sil C18 W 4.6 mm × 250 mm i.d. column and detected by UV at 210 nm. The linearity range for (a + b) boswellic acid was100-500 mg3/mL with average recovery of 98.14 ± 0.9362. The limit of detection and limit of quantification were found to be (0.01740, 0.05273, 0.01739 and 0.05270 mg3/mL) for a and b boswellic acid, respectively. The developed method was successfully applied for the assay of market formulations containing Boswellia serrata extract. A rapid and sensitive high-performance thin-layer chromatographic (HPLC) method was developed and validated for the quantitative estimation of curcumin in formulation containing Curcuma longa extracts. Simple extraction method was used for isolation of curcumin from formulation sample. The isolated samples were chromatographed by using RP-HPLC method on HiQ Sil C18 W 4.6 mm × 250 mm i.d. column and detected by UV at 420 nm. The linearity range for curcumin was 0.4 -2.4 mg3/mL with average recovery of 97.57 ± 0.5137. The limit of detection and limit of quantification was found to be 3.0196 and 9.1503 for curcumin, respectively. The developed method was successfully applied for the assay of market formulations containing Curcuma longa extracts.